The effect of graphene nanosheets on the mechanical properties of polyvinylchloride. Issue 5 (28th November 2014) - Nawaz, Khalid; Ayub, Muhammad; Ul‐Haq, Noaman; Khan, M.B.; Khan Niazi, Muhammad Bilal; Hussain, Arshad
Abstract : In this work, excellent improvement in mechanical properties was observed by incorporating graphene nanofillers in polyvinyl chloride via solution blending. About 63% increase in modulus and 19% increase in ultimate tensile strength were measured at 1.5 wt% nanofiller content while almost no drop in elongation at break was observed. POLYM. COMPOS., 37:1572–1576, 2016. © 2014 Society of Plastics Engineers